High magnetic aspects of nanosized NiZn ferrite powders synthesized by an autocombustion method - Deka, Sasanka; Date, Sadgopal K.; Joy, Pattayil Alias (9th International Conference on Ferrites (ICF-9), 2005)
Nanocrystalline NiZn ferrite, Ni0.5Zn0.5Fe2O4, having particle size in the range 6-10 mn, has been synthesized by an auto-combustion method. The nanosized ferrite powder formed at a low temperature is annealed at different temperatures in the range 473-1273 K and characterized by X-ray diffraction, vibrating sample magnetometry, Mossbauer spectroscopy, transmission electron microscopy and scanning electron microscopy. Magnetic transition temperature broadening up to 773 K is observed for the nanosized sample, compared to the T-c = 563 K for the bulk material. Critical particle diameter (D-c) is found to be similar to 40 nm at which maximum coercivity is obtained for the powder sample annealed at 973 K. Similarly, high room temperature magnetization, comparable to that of the bulk material, is obtained for the powders annealed at 1073 K, with a maximum particle size of similar to 50 nm. Very little grain growth is observed for the powders annealed above 1073 K. The results show that, optimum magnetic properties can be achieved for fine particle NiZn ferrite powders synthesized by a low-temperature auto-combustion method and processed at relatively lower temperatures.

Magnetic properties of nanosized ferrite powders synthesized by microwave-hydrothermal method - Khollam, Y. B.; Dhage, S. R.; Verma, S.; Potdar, H. S.; Deshpande, S. B.; Joy, Pattayil Alias; Date, Sadgopal K. (Ninth International Conference on Ferrites (ICF-9), 2005)
Nanosized powders of Fe3O4 and MgFe2O4 are synthesized by microwave-hydrothermal (MH) method. The ferrite powders thus obtained are characterized by powder X-ray diffraction, Mossbauer spectroscopy, scanning and transmission electron microscopies, vibrating sample magnetometer and AC magnetic susceptibility studies. Stoichiometric, nanosized (similar to 34 nm) Fe3O4 particles, having cubic symmetry with a(0) approximate to 8.39 angstrom, are obtained when molar ratio of Fe/NaOH used for the synthesis is 0.133. On the other hand, non-stoichiometric Fe3O4 is obtained when Fe/NaOH molar ratio is increased to 0.4. Though the powder XRD patterns of both stoichiometric and non-stoichiometric Fe3O4 are identical, Mossbauer spectroscopic studies showed different features in terms of asymmetry, intensity, isomer shift, etc. Saturation magnetization, M-s = 70 emu/g and coercivity, H-c = 178 Oe, at room temperature, are obtained for stoichiometric Fe3O4 powders. In the case of MgFe2O4, spherical, nanosized (similar to 3 nm) powders with cubic symmetry (a(0) approximate to 8.30 angstrom) and having very narrow size distribution are obtained under the MH conditions. The temperature and field dependent magnetic measurements on MgFe2O4 powders confirmed the existence of superparamagnetic state in this material with a superparamagnetic blocking temperature of 38 K below which typical magnetic hysteresis behaviour is observed.

Oriented growth of nanocrystalline gamma ferric oxide in electrophoretically deposited films - Bhave, T. M.; Balasubramanian, C.; Nagar, H.; Kulkarni, S.; Pasricha, R.; Bakare, P. P.; Date, Sadgopal K.; Bhoraskar, S. V. (Hyperfine Interactions, 2005)
Films of nanocrystalline gamma-Fe2O3 were deposited on silicon substrates by using the technique of electrophoretic deposition. The precursor powder was nanocrystalline gamma-Fe2O3, which was synthesized, using DC arc plasma in the oxygen ambient by vapour-vapour interaction in gas phase condensation; at a stabilized arc current of 40 A. This powder was characterized by X-ray diffraction, Transmission Electron Microscopy, Vibrating Sample Magnetometer and Mossbauer Spectroscopy. An increase in directional coercivity was observed in case of films deposited on silicon substrates, which is dramatically significant. Preferred orientation of almost similar sized nanocrystalline magnetic domains in deposited films is evident from the results of X-ray diffraction and Transmission Electron Microscopy results. The preferred alignment of the nanocrystallites seems to be responsible for the significant changes observed in magnetic properties of films.

Simple oxalate precursor route for the preparation of barium-strontium titanate: Ba1-xSrxTiO3 powders - Khollam, Y. B.; Deshpande, S. B.; Potdar, H. S.; Bhoraskar, S. V.; Sainkar, S. R.; Date, Sadgopal K. (Materials Characterization, 2005)
A simple one-step cation-exchange reaction between the stoichiometric solutions of ammonium titanyl oxalate (ATO) and barium hydroxide+strontium nitrate at room temperature (RT) is investigated successfully for the quantitative precipitation of barium-strontium titanyl oxalate (BSTO): Ba1-xSrxTiO(C2O4)(2).4H(2)O (x=0.25) precursor powders with nearly theoretical yield (greater than or equal to99%). The pyrolysis of BSTO at 730degreesC/4 h in air produced barium-strontium titanate (Ba1-xSrxTiO3; BST) powders. The characterization studies on BSTO and BST powders by using various physico-chemical techniques: micro- and chemical analysis, differential thermal analysis (DTA)/thermo-gavimetric analysis (TGA), XRD, FTIR, X-ray fluorescence (XRF) and scanning electron microscopy (SEM) revealed that the powders formed are cubic, highly pure, stoichiometric and sub-micron-sized with nearly uniform size and shape distribution. The ceramic compacts obtained by sintering the BST pellets at 1300degreesC/4 It showed density similar to95%, dielectric constant epsilon(Tc)similar to9500, tan delta-0.15% and T(C)similar to32 degreesC. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: barium-strontium titanate; barium-strontium titanyl oxalate; permittivity; XRF

Synthesis and characterization of microwave-hydrothermally derived Ba1-xSrxTiO3 powders - Deshpande, S. B.; Khollam, Y. B.; Bhoraskar, Y. B.; Date, Sadgopal K.; Sainkara, S. R.; Potdar, H. S. (Materials Letters, 2005)
Submicron-sized, spherical, stoichiometric strontium substituted barium titanate: Ba0.75Sr0.25TiO3 (BST) powders are prepared by microwave-hydrothermal (MH) route under the MH conditions of 200 degreesC, 200 psi, and 30 min in strongly alkaline conditions (pH>12) using potassium titanyl oxalate (KTO) and nitrates of Ba and Sr as the starting precursors and KOH as the mineralizer. The characterization studies by XRD, XRF and SEM indicated that stoichiometric cubic BST powders (a(0)=3.992 A) were obtained by adjusting MH conditions mentioned earlier and keeping the (Ba+Sr)/Ti ratio in starting solution slightly in excess (similar to1.06). (C) 2004 Elsevier B.V. All rights reserved.
Keywords: barium-strontium titanate; dissolution-recrystallization; Microstructure; microwave-hydrothermal synthesis; mineralizer; SEM; XRD; XRF

Synthesis and magnetic properties of polycrystalline Co-doped ZnO - Deka, Sasanka; Date, Sadgopal K.; Joy, Pattayil Alias (9th International Conference on Ferrites (ICF-9), 2005)
Nanocrystalline Zn1-xCoxO powders have been synthesized by a glycine-nitrate (GNP) and modified GNP methods. Ferromagnetism at room temperature and above is observed for the powder samples synthesized by GNP method. The saturation magnetization value at 300 K is obtained as 0.08 and 0.28 emu/g (at 1 T), respectively, for x = 0.05 and 0.1. Ferromagnetic transition occurs at 740 K and 770 K for the respective samples, which is much larger than that the reported in the literature for thin film samples. On the other hand, no ferromagnetism was observed, down to 10 K, for the compounds synthesized by the modified GNP method.

Vishnu Ganesh Bhide (1940-2006) - Ogale, Satish; Date, Sadgopal K. (Current Science, 2006)

Mossbauer spectroscopic investigations of nanophase iron oxides synthesized by thermal plasma route - Nagar, Harshada; Kulkarni, Naveen V.; Karmakar, Soumen; Sahoo, B.; Banerjee, Indrani; Chaudhari, P. S.; Pasricha, R.; Das, A. K.; Bhoraskar, S. V.; Date, Sadgopal K.; Keune, W. (Materials Characterization, 2008)
Magnetic nanoparticles of iron oxide were synthesized by transferred arc plasma induced gas phase condensation method. Structural, morphological and magnetic studies of the as synthesized powder were carried out using X-ray diffraction, transmission electron microscopy and Mossbauer spectroscopy. These studies have revealed the simultaneous nucleation and condensation of different magnetic phases with a broad size distribution of the nanoparticles which is peaked at 30-50 nm and ranges from 10 nm to 80 nm. 57 Fe Mossbauer spectra recorded at various temperatures (5 K-300 K) in presence of external magnetic field (at 5 K) have suggested the presence of different phases of iron oxide with sizable amounts of gamma-Fe2O3 and alpha-Fe2O3 in addition to Fe3O4. The relative concentrations of these phases have been obtained by a self consistent spectral area analysis and were found to be 44:22:34 (%). (C) 2007 Elsevier Inc. All rights reserved.
Keywords: iron oxides; Mossbauer spectroscopy; phase analysis; plasma synthesis

Epitaxially grown zinc-blende structured Mn doped ZnO nanoshell on ZnS nanoparticles - Limaye, Mukta V.; Singh, Shashi B.; Date, Sadgopal K.; Gholap, Ramkrishna S.; Kulkarni, Sulabha K. (Materials Research Bulletin, 2009)
Zinc oxide in the bulk as well as in the nanocrystalline form is thermodynamically stable in the wurtzite structure. However, zinc oxide in the zinc-blende structure is more useful than that in the wurtzite structure due to its superior electronic properties as well as possibility of efficient doping. Therefore, zinc oxide shell is grown epitaxially on zinc sulphide core nanoparticles having zinc-blende structure. It is shown that doping of manganese could be achieved in zinc oxide nanoshell with zinc-blende structure. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Luminescence; Nanostructures; Semiconductors; X-ray diffraction

Structure-function mimicry of oxidized purple acid phosphatase-PAP(ox)-A new functional model - Waghmode, Shobha A.; Date, Sadgopal K.; Gupta, Vidya S.; Rane, Sandhya Y. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2010)
{Electronic structure and spectroscopic properties of the novel diiron active site of oxidized mammalian purple acid phosphatase analogues, Fe-6: [Fe-2 (mu-O) (mu-OAc) (4HNSQ(ox))(2 center dot-)(ONSQ(ox))(2 center dot-)(H2O)(4)] and Fe-7: [Fe-2 (mu-O) (mu-OAc)(ONSQ(ox))(2 center dot-)(OAc) (H2O)(4)] are described. Magnetic susceptibility SQUID data of Fe-6 are best fitted to Heisenberg's isotropic spin pair (S = 5/2, 3/2) model using magnetic parameters g = 2 and J = - 36.8 cm(-1) with R factor = 6.4 x 10(-4). The antiferromagnetic exchange establishes Fe(III)-O-Fe(III) dimeric core with Fe(III) site having two radical ligations in the naphthosemiquinone oxime form of lawsone oxime. In the model compound Fe-7 of oxidized purple acid phosphatase, bridged and terminal acetate functions are identified according to their different energies of activations, i.e, similar to 34 and 58 kJ mol(-1) respectively. Also, the reduced naphthoquinone oxime form of ligand is characterized by its energy of activation (similar to 15 kJ mol(-1)) from pyrolytic reaction. Mossbauer parameters
Keywords: Antiferromagnetic exchange; Bioinorganic chemistry; DNA cleavage; iron; Nuclease activity; PAP(ox) analogues

Synthesis of low coercive BaFe12O19 hexaferrite for microwave applications in low-temperature cofired ceramic - Rane, Vivek A.; Meena, Sher Singh; Gokhale, Suresh P.; Yusuf, S. M.; Phatak, Girish J.; Date, Sadgopal K. (Journal of Electronic Materials, 2013)
Polycrystalline M-type barium hexaferrite (BaFe12O19) samples have been synthesized by solution combustion route at different pH and calcination conditions in order to reduce the coercivity for microwave applications in low-temperature cofired ceramic (LTCC) substrates. Structural, morphological, and magnetic properties of BaFe12O19 were studied by x-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), Raman spectroscopy, vibrating sample magnetometry (VSM), and Mossbauer spectroscopy. The formation of a single-phase hexagonal structure was confirmed by XRD. The Raman spectra reveal all characteristic peaks of BaFe12O19, illustrating the phase purity and crystal lattice symmetry of the synthesized material. Mossbauer spectra illustrate the existence of Fe3+ cations at all five crystallographic lattice sites. The microstructural features observed by FESEM disclose the growth of nanoregime particles into hexagonal platelet particles after calcination at temperatures from 800A degrees C to 1200A degrees C. The VSM results show a lower coercivity (1350 Oe to 3500 Oe) together with reasonably high saturation magnetization (55 emu/g to 60 emu/g) and a high bulk resistivity (> 10(9) Omega-cm) at room temperature. The dependence of magnetic and electrical properties on the preparation and processing conditions is also discussed.
Keywords: Barium hexaferrite; coercivity; LTCC; Mossbauer spectroscopy; Raman spectroscopy